Effect of Forage Sorghum on Milk Production - Somkiert Prasanpanich; Jamroen Thiengtham; Sayan Tudsri; Soar Siwichai; Theerayuth Juntanam (Agriculture and Natural Resources, 2010)
The effect of forage sorghum on dairy production was studied, using eight multiparous midlactating Holstein-Friesian crossbred cows, based on days in milk, lactation number and milk yield. They were divided into two treatments using a group comparison, with four animals in each group. Animals in Group 1 were provided with fresh sole forage sorghum, at 60 d defoliation after planting, and in Group 2 were fed fresh forage sorghum with lablab legumes at the same age as in Group 1. All cows were also supplemented with 45-50% of total daily dry matter intake with meal concentrate of 17.39% CP, twice daily at milking times of 05:00 and 15:00. The results revealed that cows fed fresh forage sorghum mixed with lablab legumes had significantly higher roughage daily dry matter intake, total daily dry matter intake, %BW of total daily roughage dry matter intake and %BW of total daily dry matter intake than Group 2 (P<0.05). The actual milk yield and 4% fat corrected milk, milk composition, blood glucose and blood urea nitrogen in the morning and afternoon feeding in both treatments were not significantly different. However, this study suggested that the higher nutritive value of forage sorghum intercropped with forage legume could increase dairy production.